On the ability of proglacial lake diatoms to reconstruct Antarctic past ozone changes - Anna Beatriz Jones Oaquim; Heitor Evangelista; Gleyci Aparecida Oliveira Moser; Marcus Vinícius Licínio; Emília Correia; Domênica Teixeira de Lima; Sergei Verkulich; Zinaida Pushina; Yuri Kublitsky (PLoS ONE, 2026)
The depletion of Antarctic stratospheric ozone since the 1970s, and the resulting increase in UV radiation reaching the Earth’s surface, have posed a well-recognized threat to polar aquatic and terrestrial ecosystems. Although this phenomenon is primarily driven by anthropogenic emissions, natural processes linked to volcanic activity and changes in solar irradiance can also influence ozone levels over time. Understanding past ozone changes over Antarctica is therefore essential for constraining the amplitude of its natural variability. Given the sensitivity of diatoms to different environmental conditions, we investigated the potential of these organisms as proxies for ozone variability by analyzing their relative abundance along a proglacial lake sediment profile dated using excess 210 Pb. We found that a specific diatom assemblage dominated by Gomphonema sp., Nitzschia cf. kleinteichiana , Humidophila tabellariaeformis , and Pinnularia borealis shows significant responses to measured ozone data from Faraday/Vernadsky station, allowing the development of a quantitative reconstruction model for the modern epoch. Applying this model to a Holocene sediment core from the same ice-free area, we obtained a millennial-scale reconstruction of past ozone variability. Our results indicate that the magnitude of recent ozone depletion is unprecedented over the past 7,700 years. These findings demonstrate the value of lake-sediment diatom assemblages as proxies for reconstructing past stratospheric ozone dynamics in Antarctica and contribute to a deeper understanding of long-term atmosphere–biosphere interactions in polar regions.